Odpowiedzi

2010-01-17T19:18:25+01:00
4y=3x-4
2x=-3(y-5)

4y=3x-4
2x=-3y+15

4y-3x=-4
2x+3y=15

12y-9x=-12
12y+8x=60 odejmownie
-x=-72
x=72

4y=216-4
4y=212
y=53
2010-01-17T19:18:38+01:00
4y=3x-4
2x=-3(y-5)

4y=3x-4
2x = -3y + 15

4y=3x-4
x = -1,5y + 7,5

4y = 3 * (-1,5y + 7,5)- 4
x = -1,5y + 7,5

4y = -4,5y + 22,5 - 4
x = -1,5y + 7,5

8,5y = 18,5
x = -1,5y + 7,5

y = 18,5/8,5
x = -1,5 * 18,5/8,5 + 7,5

y = 18,5/8,5
x = - 27,75/8,5 + 7,5
1 5 1
2010-01-17T20:04:28+01:00
4y=3x-4
2x=-3(y-5)

4y=3x-4
2x = -3y + 15

4y=3x-4
x = -1,5y + 7,5

4y = 3 * (-1,5y + 7,5)- 4
x = -1,5y + 7,5

4y = -4,5y + 22,5 - 4
x = -1,5y + 7,5

8,5y = 18,5
x = -1,5y + 7,5

y = 18,5/8,5
x = -1,5 * 18,5/8,5 + 7,5

y = 18,5/8,5
x = - 27,75/8,5 + 7,5